Biocompatible liquid-crystal elastomers mimic the intervertebral disc. (July 2020) - Shaha, Rajib K.; Merkel, Daniel R.; Anderson, Mitchell P.; Devereaux, Emily J.; Patel, Ravi R.; Torbati, Amir H.; Willett, Nick; Yakacki, Christopher M.; Frick, Carl P.
Abstract: The hierarchical and anisotropic mechanical behavior requirement of load-bearing soft tissues limits the utility of conventional elastomeric materials as a replacement for soft-tissue materials. Liquid-crystal elastomers (LCEs) have the potential to excel in this regard owing to its unique combination of mesogenic order in an elastomeric network. In this study, the mechanical behavior of the LCEs relevant to load-bearing biomedical applications was explored. LCEs with different network orientations (i.e., mesogen alignments) were investigated by fabricating the LCEs with polydomain and monodomain configurations. The polydomain and monodomain LCEs with the same degree of network crosslinking demonstrated diverse mechanical behavior, ranging from highly stiff and elastic nature to high damping capacity, depending on the loading direction with respect to the network alignment. The LCEs were also capable of matching the anisotropic mechanical behavior of an intervertebral disc. Additional studies were conducted on the in vivo biological response of LCEs upon subcutaneous implantation, as well as on the effect of the exposure to an in vitro simulated physiological environment on the mechanical behavior. The LCEs' mechanical response was negligibly affected when exposed to biomedically relevant conditions. Furthermore, the solid and porous LCEs did not show any adverse effect on the surrounding tissues when implanted subcutaneously in rats. The biological response allows for tissue ingrowth and helps illustrate their utility in implantable biological devices. Finally, the utility of LCEs to mimic the mechanical function of biological tissue such as intervertebral disc was demonstrated by fabricating a proof of concept total disc replacement device. Graphical abstract: Image 1 Highlights: Liquid crystal elastomers (LCEs) were studied for potential biomedical applications. In vivo study of solid and porous LCEs showed tissue encapsulation and ingrowth. In vitro study showed slight swelling and minimal effect on mechanical behavior. Monodomain LCEs demonstrated strong anisotropic mechanical behavior. A synthetic intervertebral disc was devised utilizing LCEs' anisotropy.